一种电子束发射装置 (2024)
本发明公开了一种电子束发射装置，旨在解决坩埚组件和电子束发射组件集成在一起，位置无法调整，使用不便的不足。该发明包括安装座、灯丝组件、磁场组件，灯丝组件包括灯丝、夹持座、整形罩，灯丝装夹在夹持座上部，整形罩套装在夹持座上部，灯丝置于整形罩内，灯丝两端通高压电，整形罩上端设有发射口；整形罩上安装电极罩，电极罩上端开口，电极罩下端设有和发射口对应的对接口；安装座上连接梭心，电极罩套装在梭心上，梭心内设有冷却流道；磁场组件包括电磁铁、分别安装在电磁铁两端的左磁轭和右磁轭，左磁轭和右磁轭上分别连接左极靴和右极靴，电极罩置于左极靴和右极靴的端部之间。 The invention discloses an electron beam emission device, and aims to overcome the defects that: a crucible assembly and an electron beam emission assembly are integrated together, the position cannot be adjusted, and use is inconvenient. The device comprises a mounting seat, a filament assembly and a magnetic field assembly, the filament assembly comprises a filament, a clamping seat and a shaping cover, the filament is clamped at the upper part of the clamping seat, the shaping cover sleeves the upper part of the clamping seat, the filament is arranged in the shaping cover, two ends of the filament are electrified with high voltage, and an emission port is formed in the upper end of the shaping cover; the shaping cover is provided with an